2015
DOI: 10.1016/j.sbspro.2015.04.098
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, Attitudes and Classroom Management: A Study on Prospective Teachers

Abstract: In this paper, the results of a study attempted to find out the attitudes and beliefs of prospective teachers studying in English Language Teaching Program (ELT) toward classroom management is presented. The study findings are based on the data gathered by utilizing the adapted form of Attitudes and Beliefs on Classroom Control Inventory administered to 280 ELT students. The data revealed that while students hold more interventionist and interactionist orientation on Instructional Management subscale, they hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 4 publications
4
16
0
Order By: Relevance
“…The practice of teacher leadership is an important aspect of improving effective classroom management practices, especially for teachers in special education as stated by Ngang et al (2015). It is teachers' responsibility to create a supportive, positive, orderly, and conducive learning environment (Caner & Tertemiz, 2015). In order to obtain those ideal circumstances, school and classroom management strategies should be developed with constructivist approaches (Erdogan & Kurt (2015)).…”
Section: Volume 1 Issue 1 Paper 10mentioning
confidence: 99%
“…The practice of teacher leadership is an important aspect of improving effective classroom management practices, especially for teachers in special education as stated by Ngang et al (2015). It is teachers' responsibility to create a supportive, positive, orderly, and conducive learning environment (Caner & Tertemiz, 2015). In order to obtain those ideal circumstances, school and classroom management strategies should be developed with constructivist approaches (Erdogan & Kurt (2015)).…”
Section: Volume 1 Issue 1 Paper 10mentioning
confidence: 99%
“…Quintero & Ramírez, 2011;Veldman, Admiraal, Mainhard, Wubbels, & Tartwijk, 2017). These authors coincide in the idea that setting up an adequate work atmosphere and dealing with challenges in the classroom is a sensitive and, at times, difficult area for every teacher, particularly for novices (Caner & Tertemiz, 2015;Fowler & Saraplı, 2010;Lewis, 2009;Macías, 2017;Macías & Sánchez, 2015;Marzano, Marzano & Pickering, 2003;Quintero & Ramírez, 2011;Sánchez, 2011a, Sánchez, 2011bPineda & Frodden, 2008;Sieberer-Nagler, 2016). Given its influence on learning outcomes, CM could be more prominent, and instruction on it could be more explicit in L2 teacher education programs, conferences and workshops for professional development.…”
Section: Classroom Management and Novice Teachersmentioning
confidence: 97%
“…Further knowledge is gained by acknowledging the challenges and consequences of not handling the dynamics of the classroom, something that has been researched from different perspectives, while highlighting the prominent role of CM in the classroom (Landau, 2001;Latz, 1992;Yerli Usul & Yerli, 2017). For some, CM is the most essential issue in a teacher's day-to-day professional practice (Wright, 2005), the most valuable set of skills instructors can have (Landau, 2001), or one of the most difficult responsibilities that teachers deal with in the classroom (Caner & Tertemiz, 2015).…”
Section: Understanding Classroom Managementmentioning
confidence: 99%
“…There are also studies that investigated the relevance and effectiveness of the classroom management courses for preservice teachers (Caner & Tertemiz, 2015;Cerit, 2011;Fowler & Sarapli, 2010;Giallo & Little, 2003;Gurcay, 2015;Weinstein, 1998). For example, Cerit (2011) explored the relationship between preservice teachers' self-efficacy and their approach to classroom management.…”
Section: Introductionmentioning
confidence: 99%
“…They found that ELT students have certain expectations of their educational leaders such as being on time for class and starting the class as scheduled. Caner and Tertemiz (2015) studied the attitudes and beliefs of preservice teachers studying in English Language Teaching Program (ELT) toward classroom management. Balli (2011) studied pre-service teachers' perspectives on classroom management strategies of their past teachers.…”
Section: Introductionmentioning
confidence: 99%